Bipolar volcanic ice-core synchronization of the entire last glacial period - Anders Svensson; Guido Vettoretti; Jia-mei Lin; Giulia Sinnl; Dorthe Dahl-Jensen; Jørgen Peder Steffensen; Sune Olander Rasmussen; Bo Vinther; Christine Hvidberg; Helle Astrid Kjær; Vasileios Gkinis; Eliza Cook; et al. (Quaternary Science Reviews, 2026)

Exploiting the Greenland volcanic ash repository to date caldera-forming eruptions and widespread isochrons during the Holocene - Siwan M. Davies; Paul G. Albert; Anna J. Bourne; Sara Owen; Anders Svensson; Matthew S.M. Bolton; Eliza Cook; Britta J.L. Jensen; Gwydion Jones; Vera V. Ponomareva; Takehiko Suzuki (Quaternary Science Reviews, 2024)

Mid-to Late Holocene East Antarctic ice-core tephrochronology: Implications for reconstructing volcanic eruptions and assessing their climatic impacts over the last 5,500 years - Peter M. Abbott; Joseph R. McConnell; Nathan J. Chellman; Sepp Kipfstuhl; Maria Hörhold; Johannes Freitag; Eliza Cook; William Hutchison; Michael Sigl (Quaternary Science Reviews, 2024)

First identification and characterization of Borrobol‐type tephra in the Greenland ice cores: new deposits and improved age estimates - Eliza Cook; Siwan M. Davies; Esther R. Guðmundsdóttir; Peter M. Abbott; Nicholas J. G. Pearce (Journal of Quaternary Science, 2018)
Contiguous sampling of ice spanning key intervals of the deglaciation from the Greenland ice cores of NGRIP, GRIP and NEEM has revealed three new silicic cryptotephra deposits that are geochemically similar to the well‐known Borrobol Tephra (BT). The BT is complex and confounded by the younger closely timed and compositionally similar Penifiler Tephra (PT). Two of the deposits found in the ice are in Greenland Interstadial 1e (GI‐1e) and an older deposit is found in Greenland Stadial 2.1 (GS‐2.1). Until now, the BT was confined to GI‐1‐equivalent lacustrine sequences in the British Isles, Sweden and Germany, and our discovery in Greenland ice extends its distribution and geochemical composition. However, the two cryptotephras that fall within GI‐1e ice cannot be separated on the basis of geochemistry and are dated to 14358 ± 177 a b2k and 14252 ± 173 a b2k, just 106 ± 3 years apart. The older deposit is consistent with BT age estimates derived from Scottish sites, while the younger deposit overlaps with both BT and PT age estimates. We suggest that either the BT in Northern European terrestrial sequences represents an amalgamation of tephra from both of the GI‐1e events identified in the ice‐cores or that it relates to just one of the ice‐core events. A firm correlation cannot be established at present due to their strong geochemical similarities. The older tephra horizon, found within all three ice‐cores and dated to 17326 ± 319 a b2k, can be correlated to a known layer within marine sediment cores from the North Iceland Shelf (ca. 17179‐16754 cal a BP). Despite showing similarities to the BT, this deposit can be distinguished on the basis of lower CaO and TiO 2 and is a valuable new tie‐point that could eventually be used in high‐resolution marine records to compare the climate signals from the ocean and atmosphere.